2020
DOI: 10.1016/j.nicl.2019.102114
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy modulates grey matter increase in a hub of an affect processing network

Abstract: HighlightsWe here present a structural neuroimaging study reporting on a large multi-site patient sample with unipolar depression that underwent ECT.Patients showed grey matter increases in the medial temporal lobe.Connectivity modeling revealed that this altered brain region was involved in networks related to affect processing and memory.This provides a potential explanation, how these structural changes during ECT are involved in both main and side effects of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Intriguingly, electroconvulsive therapy (ECT) has been identified as a potential intervention to increase hippocampal volume, global functioning, and quality of life in patients [86][87][88]. We believe these results emphasize the validity of hippocampal GMV as a transdiagnostic correlate of psychopathology that could be a target for intervention and prevention.…”
Section: Diagnoses-common Gmv Alterationsmentioning
confidence: 84%
“…Intriguingly, electroconvulsive therapy (ECT) has been identified as a potential intervention to increase hippocampal volume, global functioning, and quality of life in patients [86][87][88]. We believe these results emphasize the validity of hippocampal GMV as a transdiagnostic correlate of psychopathology that could be a target for intervention and prevention.…”
Section: Diagnoses-common Gmv Alterationsmentioning
confidence: 84%
“…due to cells) and thereby a degeneration of microstructural integrity; several investigations showed a decrease in mean diffusivity after a course of ECT favoring neuroplasticity as underlying mechanism over vasogenic edema that would be accompanied by an increased mean diffusivity due to accumulating extracellular fluids [18,50,74]. Still, an intracellular fluid/ion shift (cell swelling) induced by the seizure cannot be ruled out and would explain the reversibility of the volumetric effects [75]. Finally, response to ECT has been associated with polymorphisms of the BDNF gene [76,77], while the vascular endothelial growth factor (VEGF) gene was linked to hippocampal growth [78].…”
Section: Discussionmentioning
confidence: 99%
“…Electroconvulsive therapy (ECT), a highly effective treatment for refractory depression, is thought to be excellent for neuroplasticity (Cai et al, 2022 ). Several studies have found that electroconvulsive therapy causes a significant increase in GMV in the right amygdala (Gryglewski et al, 2019 , 2021 ; Camilleri et al, 2020 ). Our previous study confirmed that ECT can selectively increase the volume of the hippocampal-amygdala transition region bilaterally in patients with depression (Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%